Rapamycin attenuates PLA2R activation-mediated podocyte apoptosis via the PI3K/AKT/mTOR pathway - Terry Ting-Yu Chiou (Elsevier, 2021)
Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in adults without diabetes. Primary MN has been associated with circulating antibodies against native podocyte antigens, including phospholipase A2 receptor (PLA2R); however, precision therapy targeting the signaling cascade of PLA2R activation is lacking. Both PLA2R and the mammalian target of rapamycin (mTOR) exist in podocytes, but the interplay between these two proteins and their roles in MN warrants further exploration. This study aimed to investigate the crosstalk between PLA2R activation and mTOR signaling in a human podocyte cell line. We demonstrated that podocyte apoptosis was induced by Group IB secretory phospholipase A2 (sPLA2IB) in a concentration- and time-dependent manner via upregulation of phosphoinositide 3-kinase (PI3K), protein kinase B (AKT), and mTOR, and inhibited by rapamycin or LY294002. Furthermore, aberrant activation of the PI3K/AKT/mTOR pathway triggers both extrinsic (caspase-8 and caspase-3) and intrinsic (Bcl-2-associated X protein [BAX], B-cell lymphoma 2 [BCL-2], cytochrome c, caspase-9, and caspase-3) apoptotic cascades in podocytes. The therapeutic implications of our findings are that strategies to reduce PLA2R activation and PI3K/AKT/mTOR pathway inhibition in PLA2R-activated podocytes help protect podocytes from apoptosis. The therapeutic potential of rapamycin shown in this study provides cellular evidence supporting the repurposing of rapamycin for MN treatment.